DESAIN KURIKULUM PENDIDIKAN AGAMA ISLAM (PAI) DI SEKOLAH DAN MADRASAH: KONSEP, MODEL, DAN IMPLEMENTASI KONTEKSTUAL - pratama, Riki Adi; Agus Pahrudin; Agus Jatmiko; Koderi; Imam Syafe’i (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to examine the curriculum design of Islamic Religious Education (PAI) in schools and madrasahs, focusing on its conceptual foundation, models, and contextual application within the socio-cultural setting of Lampung Province. The study adopts a library research approach by reviewing academic literature, books, and nationally accredited journals. The findings indicate that both schools and madrasahs share a common goal in developing students’ moral and spiritual character, yet differ in institutional orientation and curriculum management. Schools tend to integrate Islamic values into general subjects, while madrasahs position Islamic education as the core of the curriculum. The ideal curriculum design should be rooted in the principles of the Qur’an and Hadith, such as the command to educate with wisdom and good example (Qur’an, An-Nahl: 125), as well as the Prophet’s sayings on the significance of moral education. Thus, an integrative curriculum model that harmonizes knowledge, spirituality, and character becomes the strategic direction for PAI curriculum development in Lampung to remain responsive to local socio-cultural dynamics.